Manajemen Kelas Dalam Meningkatkan Mutu Pembelajaran Di MAS Tarbiyah Islamiyah Kecamatan Hamparan Perak Kabupaten Deli Serdang - Abrianto, Danny; Tumiran, Tumiran; Pangabean, Hadi Syahputra; Sembiring, Rizky Aji Akbar (Yayasan Rahmat Islamiyah, 2023)
This research raises the phenomenon that occurs among teachers and students, especially MAS Tarbiyah Islamiyah Hamparan Perak students with several problems that occur, namely regarding teachers' efforts to improve the quality of learning and learning motivation through classroom management. This type of research is qualitative, descriptive in nature. Data sources were obtained from primary data (directly) through in-depth observations, interviews at MAS Tarbiyah Islamiyah Hamparan Perak through a combination of techniques. The data analysis technique used was using the Miles and Humberman theory. The research results show that in implementing classroom management, teachers have skills in formulating and designing learning plans to improve the quality of learning and strive to achieve the school's vision and mission, so that teachers are able to organize classes and master various classroom management strategies that suit students and teachers are able to vary learning methodologies that are active, innovative, creative and fun. In this way, teachers are able to carry out monitoring and evaluation of learning as feedback in teaching and learning activities. Success in implementing classroom management in improving the quality of learning is marked by an increase in motivation in student learning outcomes in the classroom.